TARI BEDAYAN PADEPOKAN TUGUREJO DI DESA SRAGI KECAMATAN TALUN KABUPATEN BLITAR SEBAGAI EKSPRESI KOMUNITAS - Windari Astuti (Greget, 2015)
The performance of the Bedayan Dance of PadepokanTugurejois an example of an art formfrom Padepokan Tugurejo which continues to exist today. The Bedayan Dance ofPadepokanTugurejo, which has a duration of 30 minutes, is a tool or bridge for the community ofPadepokan Tugurejo to channel their own individual expression of the soul. The questions addressed in the research, amongst others, are what is the form of the Bedayan Dance ofPadepokanTugurejo and why is the expression of the community formed through this dance. Themethod used to answer these questions is a qualitative descriptive research method in which thedata was collected through the steps of direct observation, interviews, and a library study. Thetheoretical foundation used is based on the theories of Y.SumandyoHadiandStephanieRoss. Theresults of the research show that the lack of interest among the young generation in the continuation of this art form means that the performance of this art continues to be given by members ofthe older generation. Through the Bedayan Dance of PadepokanTugurejo, it is possible to form theexpression of the soul of the artists from PadepokanTugurejo.Keywords:Bedayan PadepokanTugurejo, Form of Performance, Expression, Community.